On ϕ-Recurrent Para-Sasakian Manifold Admitting Quarter-Symmetric Metric Connection. (16th February 2012) - Pradeep Kumar, K. T.; Venkatesha,; Bagewadi, C. S.
Abstract : We obtained the relation between the Riemannian connection and the quarter-symmetric metric connection on a para-Sasakian manifold. Further, we study ϕ -recurrent and concircular ϕ -recurrent para-Sasakian manifolds with respect to quarter-symmetric metric connection.